Microbial Resistance Caused by Antibiotic Prophylaxis with Amoxicillin in a Male Infant with Vesicoureteral Reflux - Taniguchi, Kazuto; Kii, Sakumo; Oka, Masafumi; Uemichi, Kazuyasu (Journal of Nepal Paediatric Society, 2018)
Vesicoureteral reflux is a common condition in infants with urinary tract infection. Although antibiotic prophylaxis to prevent recurrent urinary tract infection is widely performed, its effectiveness remains controversial. Herein we report a seven- month-old boy with vesicoureteral reflux. Antibiotic prophylaxis with amoxicillin caused microbial resistance accompanied by recurrent urinary tract infection. Subsequent antibiotic prophylaxis with sulfamethoxazole-trimethoprim was effective until spontaneous remission of vesicoureteral reflux occurred. Sulfamethoxazole-trimethoprim, but not amoxicillin, should be considered as an agent for antibiotic prophylaxis in infants with vesicoureteral reflux.